Asia –Facific Trade and Investment Report 2017 : Channeling Trade and Investment into Sustainable Development (United Nations, 2017)
Reports on trends and developments in trade, investment and regional integration in the Asia-Pacific region; emerging issues in trade, investment and trade facilitation policies, and the impacts of these policies on countries' abilities to meet the challenges of achieving inclusive and sustainable development.